PENGARUH PEMBELAJARAN KEWIRAUSAHAAN DAN PRAKTIK KERJA INDUSTRI (PRAKERIN) TERHADAP SIKAP KEWIRAUSAHAAN SISWA SMK NEGERI DI SURABAYA - Sulistyowati, Raya (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2014)
This study aims to Determine the effect of learning and working practices of industrial entrepreneurship (prakerin) on entrepreneurial attitudes in students of SMK Negeri Surabaya. This research is quantitative. The technique used is to test the hypothesis using regression analysis. The results of the study Showed that the value of the regression coefficient of entrepreneurial learning and industry work practices Significantly influence the entrepreneurial attitude of students of SMK Negeri Surabaya, meaning Prakerin implementation and entrepreneurial learning is an important part in shaping the entrepreneurial attitude of students of SMK Surabaya State